Long-term outcomes of mesohepatectomy for centrally located liver tumors: two-decade single-center experience - Mehrabi, Arianeb; Ramouz, Ali; Golriz, Mohammad; Khajeh, Elias; Hackert, Thilo; Müller, Beat P.; Strobel, Oliver; Hoffmann, Katrin; Büchler, Markus W.; Ünal, Umut Kaan; Ghamarnejad, Omid; Mieth, Markus; et al. (Journal of the American College of Surgeons, 2022)
Export - BACKGROUND: Mesohepatectomy is a viable treatment option for patients diagnosed with centrally located liver tumors (CLLTs). There are several reports from Eastern centers, but few data are available on this topic from Western centers. - STUDY DESIGN: - Data of 128 consecutive patients who underwent mesohepatectomy between September 2000 and September 2020 in our center were analyzed from a prospectively collected database. Patient demographic data, liver tumor characteristics, and intraoperative data were collected. In addition, posthepatectomy bile leakage (PHBL), posthepatectomy hemorrhage (PHH), posthepatectomy liver failure (PHLF), and 90-day mortality after mesohepatectomy were assessed. Long-term outcomes were also reported, and factors that may influence disease-free survival were evaluated. - RESULTS: - Of 128 patients, 113 patients (88.3%) had malignant hepatic tumors (primary and metastatic tumors in 41 [32%] and 72 [56.3%] patients, respectively), and 15 patients suffered from benign lesions (11.7%). Among the relevant surgical complications (grade B or C), PHBL was the most common complication after mesohepatectomy and occurred in 11.7% of patients, followed by PHLF in 3.1% of patients and PHH in 2.3% of patients. Only four patients (3.1%) died within 90 days after mesohepatectomy. The 5-year overall survival and overall recurrence (for malignant lesion) rates were 76.5% and 45.1%, respectively. - CONCLUSION: - Mesohepatectomy is a safe and feasible surgical treatment with low morbidity and mortality for patients with CLLT. Long-term outcomes can be improved by increased surgical expertise.
Members of the Liver Cancer Center Heidelberg (LCCH): Umut Kaan Ünal, Omid Ghamarnejad, Markus Mieth, Sepehr Abbasi Dezfouli, Department of General, Visceral, and Transplantation Surgery, Heidelberg University Hospital, Heidelberg, Germany; Karl Heinz Weiss, Liver Cancer Center Heidelberg and Department of Internal Medicine, Heidelberg University Hospital, Heidelberg, Germany; De-Hua Chang, Liver Cancer Center Heidelberg and Department of Interventional Radiology, Heidelberg University Hospital, Heidelberg, Germany; Christoph Springfield, MD, Liver Cancer Center Heidelberg and National Center for Tumor Diseases, Department of Oncology, Heidelberg University Hospital, Heidelberg, Germany; Benjamin Goeppert, MD, Thomas Longerich, MD, Liver Cancer Center Heidelberg and Institute of Pathology, Heidelberg University Hospital, Heidelberg, Germany
Christoph Springfeld ist in der Vorlage fälschlich als Christoph Springfield angegeben
Gesehen am 30.08.2022